30 Rock - Season 5 Episode 1-23 - Scardino, Don; MacCarthy-Miller, Beth; Riggi, John; Clark, Matthew; Fey, Tina; Baldwin, Alec; Morgan, Tracy (Universal Pictures, 2016)
Emmy Award-winner Tina Fey (Saturday Night Live) writes, executive-produces and stars as writer Liz Lemon in "30 Rock", an Emmy-winning, irreverent, and wildly funny workplace comedy set behind-the-scenes of a live variety show. "30 Rock" is told through the comedic voice of Fey and features the inimitable and Oscar-nominated Alec Baldwin as Jack Donaghy, the brash network executive who turns Liz's show (and life) upside down with his meddling ways. Set in New York City, this smart and popular series also stars Tracy Morgan, Jane Krakowski, Scott Adsit, and Jack McBrayer, and boasts a cavalcade of guest appearances from some of the most respected and recognisable faces in comedy. [www.amazon.co.uk]